Pengaruh Ketebalan dan Frekuensi Pembalikan dalam Penjemuran Rumput Laut Gracilaria sp - Mursalim Mursalim; Samsuar Samsuar; sitti aisah (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2021)
Marketing of seaweed is still in the form of dried seaweed, but in fact the quality of the dried seaweedthat is sold by farmers has not met the standards required by the seaweed processing industry. One ofthe efforts that can be made to improve the quality of dried seaweed is by optimizing drying, namelyby adjusting the thickness and reversal frequency. Pile thickness of will determine the length of timedrying is carried out, while the frequency of reversal will determine the spread of heat that occurs inthe seaweed pile. The aim of this study was to determine the drying speed in seaweed Gracilaria spdrying and quality of dried sweaweed. The study was conducted with two treatments, namely pilethickness of 12, 16 and 20 cm and treatment of reversal frequency with an interval of 3 hours, 4 hoursand 5 hours. The parameters observed in this study were a decrease in water content, drying rate, andsensory test. The results showed that the drying of Gracilaria sp seaweed with a thicknessof 12 cm with a reversal frequency of each 3-4 hours is the best treatment in terms of color / brightnessand good texture with a drying rate of 0.462 kg H2O/kg solids hour.